PATTERNS OF PRESENTATION AND OUTCOME IN CRITICAL LIMB ISCHEMIA: Critical Limb Ischemia - ., Sqn L Dr Shahrukh Tariq; ., Nauman Imtiaz; ., Faran Kiani; Malik, Zaka Ullah; ., Irfan Shukr (Pakistan Armed Forces Medical Journal, 2013)
Introduction: The threatened limb due to peripheral occlusive arterial disease, embolism or trauma requires early recognition and urgent treatment if the limb is to be saved.Objective: To determine the pattern of presentation and outcome of surgery in cases of critical limb ischemia.Study Design: Descriptive study.Place and Duration of Study: This study was conducted at surgical ward, Combined Military Hospital, Rawalpindi, from Dec 2006 to Dec 2007.Subject and Methods: A sample size of 30 patients was taken by convenience sampling. Informed written consent was obtained from all patients. Patients suffering from rest pain with ischemia features, trophic lesions, extensive gangrene , ulcers and demonstrable presence of occlusive arterial disease were included in the study. Moribund patients, extensive cardiopulmonary disease or advanced malignancy were not included in the study.Results: Thirty patients were included in the study. The mean age was 56 ±13. There were 28 males (93.3%) and 2 females (6.7%). They were all married and belonged to middle and low middle social economic class. Out of 30, there were 2 (6.7%) cases of trauma while 28 (93.3%) had peripheral vascular involvement secondary to thromboembolism. Vessels involved were femoral artery in 9 (30%) cases, popliteal artery in 18 (60%) cases and brachial artery in 2 (6.7%) cases. Rest pain was present as a primary feature in all the patients (100%), while tissue loss or gangrene was seen in 22 (73.33%) cases. A total of 14 (46.7%) amputations, 6 (20%) bypass procedures, 4 (13.3%) lumbar sympathectomies, and 2 (6.7 %) embolectomies, were carried out, whereas 4 (13.3%) patients were managed conservatively. Of the patients having rest pain 46.7 % were amputated, whereas of patients having ischemic tissue loss 73.3% were amputated. 13 patients who underwent primary amputation had ankle brachial pressure index (ABPI less than 0.4 (86.7%). ABPI was more than 0.4 in 4 (13.3%) patients whereas it was less than 0.4 in 26 (86.7%) patients.Conclusion: Overall, critical leg ischemia has a very poor prognosis. If surgical, or endovascular, improvement of the blood supply to the leg is not provided in due course; half of the legs will be amputated within a year. One of the main goals of vascular surgery is to prevent major amputations.